NTU carbon footprint framework for universities - Evers, Vanessa (2024)
This report offers insight into current approaches and frameworks that are developed and adopted by universities worldwide to measure their carbon footprint (CFP). Available CFP measuring tools are assessed and an analysis of contributing emission sources that are specific to institutes of higher education (IHE) is presented. The report also evaluates (1) university rankings and their underlying parameters, (2) the homogeneity of CFP information reported by universities, (3) the contribution of emission sources to total CFP, (4) a study of specific approaches implemented by universities to reduce carbon emissions, and (5) an evaluation of the key factors that influence the overall CFP of a university. A possible framework for measuring CFP that is specific to NTU and generally applicable to universities worldwide is provided. Finally, the report identifies strategies for behavioral change and helps overcome the current gaps in collecting CFP-relevant information for universities.